Pengaruh Kecepatan Pengadukan Dan Laju Pemanasan Sintering Pada Pembuatan Trikalsium Fosfat Berpori dengan menggunakan Metode Starch-Konsolidation - Firmansyah, R; Fadli, A; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Porous tri calcium phospate (TCP) has been prepared by starch-consolidation method using wheat as the pore formed agent. The purpose of this research is to investigate the influence of agitation rate and sintering temperature rate on physical, chemical, and mechanical properties of porous TCP. Wheat particles were mixed with TCP suspension then stirred for 1 hour. The slurry was dried in oven at 80˚C for 24 hours and at 120˚C for 8 hours. The green bodies were sintered at 2, 5, and 8˚C/minutes. The obtained green bodies shown shrinkage in the range 55.29-58.97%. The compressive strength of sintered bodies resulted was 0.73 MPa at 81.93% porosity and 2.89 MPa at 60.99% porosity.Keywords: tricalcium phosphate; porosity wheat particles; compressive strength